PHotovoltaic Properties of Ultra-Small Copper Oxide Nanoparticles (Journal of the College of Basic Education, 2026)
Copper oxide (CuO) nanoparticles were synthesized chemically using aqueous copper nitrate by sol-gel method. The phase and structure investigations by XRD and SEM indicate to the spherical aggregation particles with an average particle size of 12 nm. The produced CuO nanoparticles showed an excellent purity, as confirmed by EDX measurement. The optical properties of Uv-Vis spectroscopy displayed a highly absorption band in range of 200 nm -350 nm of a bandgap 3.5 eV. These results support the preparation of these nanostructures for solar cell applications. The heterojunction (Ag/CuO/Si/Ag) characterized in term of current-voltage propertiesof as a solar cell. It displayed a filling factor (F.F) and a power conversion efficiency (η) were 48.05% and 0.105% respectively.